Welcome to our community

Be a part of something great, join today!

Use algebraic manipulation to prove the distributivity property

shamieh

Active member
Sep 13, 2013
539
Use algebraic manipulation to prove that x+yz=(x+y)(x+z) Note that this is
the distributive rule,

So I have:

(x + y)(x + z) = xx + xz + xy + zy
= x + xz + xy + zy
= x(1 + z + y) zy
=x * 1 + (z + y)(zy)
= x + ((zzy + yzz)
= x +y + z?


but i need x + yz... But I don't understand what is going on in the right side
 

Deveno

Well-known member
MHB Math Scholar
Feb 15, 2012
1,967
I don't understand what you are doing, either.

(x + y)(x + z) = (x + y)x + (x + y)z

= xx + yx + xz + yz = xx + xy + xz + yz (since xy = yx)

= x + xy + xz + yz (since xx = x)

= x(1 + y + z) + yz =...?